Fish is fish. Leo Lionni - Lionni, Leo, 1910-1999. (New York, Pantheon Books, 1970)
When his friend, the tadpole, becomes a frog and leaves the pond to explore the world, the little fish decides that maybe he doesn't have to remain in the pond either.
G4
Keywords: Fishes -- Fiction; Frogs -- Fiction